Pemahaman Tasawuf pada Psikologi Siswa dalam Perspektif Ibnu Arabi - Alfaaza, Muhammad Farih; Masnawati, Eli (TSAQOFAH, 2024)
This research aims to analyze the psychological problems experienced by today's students and offer solutions based on Ibn Arabi's Sufism perspective. The method used is qualitative research with a library research approach, which involves collecting data from various literature, books, journals and other written sources. Descriptive analysis is used to describe and interpret the data collected. The research results show that academic stress, the negative impact of technology and social media, and bullying are some of the main psychological problems experienced by today's students. Ibn Arabi's Sufism perspective offers solutions that can help students overcome these problems. The concept of Sufism emphasizes the importance of a spiritual relationship with Allah, self-purification (tazkiyah an-nafs), and control of desires, which can help students develop emotional balance and inner calm.